2013
DOI: 10.1111/cmi.12145
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cytoskeleton remodelling in dendritic cells following invasion byToxoplasma gondiicoincides with the onset of a hypermigratory phenotype

Abstract: SummaryHost cell manipulation is an important feature of the obligate intracellular parasite Toxoplasma gondii. Recent reports have shown that the tachyzoite stages subvert dendritic cells (DC) as a conduit for dissemination (Trojan horse) during acute infection. To examine the cellular basis of these processes, we performed a detailed analysis of the early events following tachyzoite invasion of human monocyte-derived DC. We demonstrate that within minutes after tachyzoite penetration, profound morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
161
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 60 publications
(175 citation statements)
references
References 45 publications
(86 reference statements)
13
161
0
1
Order By: Relevance
“…Several studies have demonstrated that immune cells infected with T. gondii become hypermotile (27)(28)(29)(30)(31)(32)(33)(34)41), an effect that has been proposed to facilitate the dissemination of the intracellular parasite in the infected host. In the present study, we have demonstrated that the hypermotility of T. gondii-infected human monocytes is linked to a dysregulation in integrin-dependent cell adhesion through defects in FAK-regulated focal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that immune cells infected with T. gondii become hypermotile (27)(28)(29)(30)(31)(32)(33)(34)41), an effect that has been proposed to facilitate the dissemination of the intracellular parasite in the infected host. In the present study, we have demonstrated that the hypermotility of T. gondii-infected human monocytes is linked to a dysregulation in integrin-dependent cell adhesion through defects in FAK-regulated focal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that the two cell types exhibited dramatically dif- (Varughese, Kasper, Anneken, & Yadav, 2015). Additionally, because redistribution of β1-integrins is observed upon T. gondii infection in DCs (Weidner et al, 2013), it is also possible that FAK dysregulation impacts on β1-integrin signalling and focal adhesion reorganisation in endothelial and epithelial cells and that the resulting increased vascular or epithelial permeability facilitates passage of T. gondii (Izawa et al, 2017). Alternatively, toxoplasma-derived regulatory molecules or phosphatases delivered to the host cell cytosol upon host cell invasion could mediate the observed effects (Daher et al, 2007;Delorme, Garcia, Cayla, & Tardieux, 2002;Gao et al, 2014;Gilbert, Ravindran, Turetzky, Boothroyd, & Bradley, 2007).…”
Section: Reduced Phosphorylation Of Fak In Caco2 Cells and Mbecs Upmentioning
confidence: 92%
“…These in turn are infected by Toxoplasma and become hypermigratory, a process that increases their emigration from the intestine to peripheral tissues [11]. Parasite induction of hypermigratory dendritic cells and inflammatory monocytes is a multi-step process that includes alterations of the host cells’ actin cytoskeleton, upregulation of the CCR7 chemokine receptor, and activation of gamma-aminobutyric acid (GABA) receptor signaling [12, 13]. …”
Section: Transit To and Entry Into The Nervous Systemmentioning
confidence: 99%